Efeitos das formulações nanoestruturadas de doxorrubicina e cisplatina em dispersão de óxido de grafeno reduzido no tratamento da progressão do câncer de bexiga Não-músculo invasivo - Villela, Renata Abreu [UNESP] (2015)
Bladder cancer is the most common malignancy of the urinary tract. The recommended first-line treatment for non-muscle invasive bladder cancer (NMIBC) following transurethral resection, is an induction course plus maintenance with intravesical Bacillus Calmette-Guerin (BCG). However, BCG immunotherapy causes undesirable effects, which contributes to treatment interruption, increasing cancer index recurrence. In this context, graphene oxide (GO) and/or reduced graphene oxide (rGO) has attracted increasing interest in the field of biological detection, drug delivery and cancer therapies. Thus, the aim of this study was to characterize and to compare the antitumor effects of Doxorubicin (DOXO) and Cisplatin (CIS) functionalized in rGO on dispersion with Pluronic F-68 polymer to the treatment of NMIBC. Initially, the characterization of the compound guarantee its chemical properties. It was used 30 female Fischer 344 rats, consisting a control group of five animals (Group 1), which received 0.3 ml of saline 0.9% intraperitoneally (i.p.). The remaining animals received 1.5 mg/kg of N-methyl-N-Nitrosourea (MNU) intravesical (i.v.) and after four doses, they were divided into five groups: Cancer Group (Group 2), Cancer + rGO Group (Group 3), Cancer + rGO + CIS Group (Group 4), Cancer + rGO + DOXO Group (Group 5), Cancer rGO + CIS + DOXO Group (Group 6), which received, respectively: the same treatment as group 1; received 0.2 mL dose at a concentration of 0.2mg/ml; received 0.2 mL of rGO dispersion with 0.05mg CIS; received 0.2 mg of DOXO in 0.2 mL of the dispersion; received 0.2 mL of rGO dispersion with the same chemotherapy combinations that groups 4 and 5. All treatments were i.p., with weekly administration during six consecutive weeks. After 16 weeks of treatment, urinary bladders were collected for histopathological, immunohistochemical and biochemical analysis, and still, blood collected for performing biochemical analyzes to obtain ...